The Effect of Barnacle Stickers (Balanus sp) on the Body of Fishing Vessels on the Sailing Speed of Ships at Sea in Sibolga City - Warnita Siahaan; Mutiara Alkayakni Harahap; Kurniawan Fazri (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
This research aims to investigate the impact of barnacle attachment (Balanus sp.) on the operational performance of fishing vessels in Sibolga City, focusing on vessel sailing speed and fuel oil consumption. The research used an experimental method with three hull condition treatments: clean hull, hull with moderate coverage (<50%), and hull with severe patch (>50%). Data collected includes speed, distance traveled, cruise time, and fuel usage. Data analysis involved ANOVA (Analysis of Variance) and simple linear regression. The results showed that barnacle patches significantly influenced ship performance (p=0.000). Ships with clean hulls achieved the highest average speed of 7.82 knots, while ships with severe sticking had the lowest speed. Regression analysis (R2=0.581) confirmed that 58. The level of barnacle attachment caused 1% of the variation in ship speed. Increasing barnacle coverage significantly increases fuel consumption through increasing hydrodynamic drag on the ship's hull. This study concludes that the presence of barnacles substantially reduces the performance and operational efficiency of fishing vessels